The Influence of Employment Status, Education, and Age at First Marriage on Fertility in South Kuta District - Ni Kade Rahma Dwi Laksmi (International Journal of Management Research and Economics, 2024)
High fertility can cause an increase in population which can have negative impacts such as social and economic inequality, increased competition for resources and jobs if it is not balanced with quality human resources. The aim of this research is to analyze the influence of employment status, education and age at first marriage on the fertility of women of childbearing age in South Kuta District. Determining the sample in this study used a purposive sampling technique with a sample size of 99 people. The types of data used are quantitative and qualitative data with primary and secondary data sources. The data collected was then analyzed using multiple linear regression analysis with the SPSS 29 program. The results of the study found that 1) Employment status, education and age at first marriage simultaneously influence the fertility of women of childbearing age in South Kuta District. 2) Employment status, education and age at first marriage have a partial negative effect on the fertility of women of childbearing age in South Kuta District. The implications of this research consist of theoretical and practical implications. Theoretically, this research supports the concept of time allocation theory and family economics which explains that decisions regarding fertility are influenced by economic considerations. The practical implications of the results of this research are that it can be used as material for consideration and input in managing population issues more effectively so as to improve the overall welfare of society in South Kuta District.